THE EFFECTIVENESS OF MAKE A MATCH TECHNIQUE WITH QR CODE-BASED FLASHCARDS ON STUDENTS’ VOCABULARY MASTERY - Diantia Cahya Rimandani; Nina Sofiana (IKIP Siliwangi, 2024)
Vocabulary is one of the most crucial components that students should have. However, the students have limited vocabulary. As a result, the students have difficulty remembering the new words. The aim of this research was to determine the effectiveness of the Make a Match Technique with QR Code-based Flashcards on vocabulary mastery for seventh-grade students at MTs Miftahul Huda Bulungan. This research used a true-experimental design with a pre-test post-test design. The population of this research was seventh-grade students. The sample of the research was 2 classes, experimental class (VII B) and control class (VII A). Data were acquired using multiple-choice tests. The researcher employed the t-test to analyze the data. Students in the experimental class had an average score of 81.73, whereas those in the control class was 71.67. Then, The Sig. (2-tailed) was 0.000, which is less than 0.05, and the T-test was greater than the T-table (5.542 > 1.697). The result showed that using Make a Match Technique with QR Code-based Flashcards was effective for improving students’ vocabulary.